The stock market effects of Islamist versus non-Islamist terror - Gan Jin; Md Rafiul Karima; Günther G. Schulze (University of Freiburg, Department of International Economic Policy (iep), 2024)
We are the first to analyze the effect of terror on stock markets by terror ideology. Surprisingly, we find that Islamist terror attacks created significant negative abnormal returns in American and European markets, but the stock market effects of other terror attacks were almost nil. For our sample of all 124 terrorist attacks in the US and Europe in the period 1994 to 2018 that caused at least five fatalities or ten injured people, we show that Islamist terror attacks are given significantly more air time (also after controlling for attack characteristics and the media pressure of competing news stories). This, however, explains only part of the differential effect of Islamist attacks on the stock markets.
Keywords: D74; F52; G10; G40; H56; 330; Terror; stock market; event studies; Islamist terror; media